DEVELOPMENT OF DIGITALIZATION OF EARLY CHILDREN LEARNING AT TK AL-HIDAYAH 25 AJUNG JEMBER - Ela Windi Safitri; Yasuli Bindulem; Nurul Anam; Ratri Kurnia Pratiwi (International Conference on Humanity Education and Society (ICHES), 2023)
Modern learning is marked by the delivery of material using digital media. Digital media is an important learning component in early childhood education institutions. Therefore, this study aims to determine the development of digitalization of early childhood learning on the "theme of the police profession" at TK Al-Hidayah 25, Ajung District, Jember Regency in 2021/2022. The research method uses R&D and the development model uses the ASSURE Model. Methods of data collection using questionnaires, observation, interviews, and documentation. Data analysis using statistical analysis and Miles&Haberman. The results of this study indicate: that this development includes the process of analyzing the characteristics of students; determine KD (Basic Competency); choosing media, teaching materials and methods; designing and using media and learning materials in IT (information and technology) media; involving students in the learning process using the Profession Theme media; and evaluating and revising the developed Professional Theme media products;